Edward L. Thorndike papers - Thorndike, Edward L. (Edward Lee), 1874-1949.; Lorge, Irving, 1905-1961.; Thorndike, Edward L. (Edward Lee), 1874-1949.
Correspondence, speeches, lectures, articles, research notes, and other papers pertaining to Thorndike's studies in educational psychology. Includes his book titled A Semantic Count of English Words (1938), coauthored with Irving Lorge.
Educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Educational psychology; English language -- Semantics; English language -- Word frequency; Educators